2020
DOI: 10.1007/s12035-020-02149-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Neurological Manifestations of COVID-19 Infection: a Mechanistic View

Abstract: There is increasing evidence of neurological manifestations and complications in patients with coronavirus disease 19 (COVID-19). More than one-quarter of patients with COVID-19 developed various neurological symptoms, ranging from headache and dizziness to more serious medical conditions, such as seizures and stroke. The recent investigations introduced hyposmia as a potential early criterion of infection with COVID-19. Despite the high mortality and morbidity rate of COVID-19, its exact mechanism of action a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 120 publications
2
57
0
Order By: Relevance
“…On October 7, 2020 searching on PubMed "COVID-19 OR COVID-2019 OR severe acute respiratory syndrome coronavirus 2 OR severe acute respiratory syndrome coronavirus 2 OR 2019-nCoV OR SARS-CoV-2 OR 2019nCoV OR (Wuhan AND coronavirus) AND brain" we found 1,293 papers and most of them showed that SARS-CoV-2 invades the CNS, developing neurological impairments such as stroke, epilepsy, anosmia and hypogeusia, seizures, and encephalitis (1,66,(233)(234)(235)(236). Specifically, a retrospective analysis by Mao et al (237) underlined that about 40% of SARS-CoV-2 patients developed headache, disturbed consciousness, and other brain dysfunction symptoms (1), and an autopsy study reported the presence of edema in brain tissue of SARS-CoV-2 patients (66).…”
Section: Brainmentioning
confidence: 99%
“…On October 7, 2020 searching on PubMed "COVID-19 OR COVID-2019 OR severe acute respiratory syndrome coronavirus 2 OR severe acute respiratory syndrome coronavirus 2 OR 2019-nCoV OR SARS-CoV-2 OR 2019nCoV OR (Wuhan AND coronavirus) AND brain" we found 1,293 papers and most of them showed that SARS-CoV-2 invades the CNS, developing neurological impairments such as stroke, epilepsy, anosmia and hypogeusia, seizures, and encephalitis (1,66,(233)(234)(235)(236). Specifically, a retrospective analysis by Mao et al (237) underlined that about 40% of SARS-CoV-2 patients developed headache, disturbed consciousness, and other brain dysfunction symptoms (1), and an autopsy study reported the presence of edema in brain tissue of SARS-CoV-2 patients (66).…”
Section: Brainmentioning
confidence: 99%
“…Reported manifestations include loss of taste and smell, headache, dizziness, Guillain-Barre syndrome, seizures, stroke and encephalitis . 3 The relatively high frequency of neurological sequelae together with the wide spectrum of symptoms raised significant concern. Some authors suggested this may be related to compromised brainlung-brain axis that facilitates induction of brain injury as a result of concurrent lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups have focused on the explanation of neurological manifestations of COVID-19 via its neuroinvasive potential (Farhadian et al 2020 ; Li et al 2020 ; Moriguchi et al 2020 ; Sepehrinezhad et al 2020 ). An increasing amount of evidence suggests the neuro-invading potential of SARS-CoV-2, which may lead to clinical symptoms and brain damage (Najjar et al 2020 ; Wood 2020 ; Zangbar et al, 2021 ). The hypothesis of the SARS-CoV-2 invasion into the CNS has been supported by studies on the coronaviruses that caused previous outbreaks (Sepehrinezhad et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%